Review of the genus Cyrtosia Perris (Diptera: Mythicomyiidae: Platypyginae) in Iran, with description of three new species - Gharali, Babak; Evenhuis, Neal (Zootaxa, 2017)
The genus Cyrtosia in Iran is reviewed and includes the description of three new species: C. bispermatheca sp. nov., C. baccadomus sp. nov. and C. zieglerii sp. nov. from northern Iran; and presents a key to species known to occur in Iran. Notes on C. meridionalis Rondani, 1863 and C. pusilla Loew, 1873, both previously recorded from Iran, are also provided.